2015
DOI: 10.5937/ratpov51-7201
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fruit maturity stages and seed extraction time on the seed quality of eggplant (Solanum melongena L.)

Abstract: Eggplant (Solanum melongena L.) is a vegetable from Solanaceae family and its fruit is used in human consumption. It is produced from seedlings in the Republic of Serbia and quantity of seed used for seedlings depends on germination and 1000 seed mass, and ranges from 250 to 350 g ha-1. The aim of this paper was to determine effect of fruit maturity stages and storage duration of harvested fruit on eggplant seed quality. Seed was extracted from technologically mature, semi-mature and botanically mature fruit. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 6 publications
2
3
0
1
Order By: Relevance
“…The weight of 1000 seeds extracted from semi-ripe fruits ranged from 2.55 to 2.84 g, while seeds from fully ripe fruits were the heaviest -from 4.16 to 4.42 g (Table 2). These results are in accordance with the ones obtained by Takač et al (2015). Demir et al (2002) reported that the weight of 1000 seeds of eggplant ranged from 4 to 5 g and reached its maximum 70 days after fertilization.…”
Section: The Weight Of 1000 Seedssupporting
confidence: 92%
“…The weight of 1000 seeds extracted from semi-ripe fruits ranged from 2.55 to 2.84 g, while seeds from fully ripe fruits were the heaviest -from 4.16 to 4.42 g (Table 2). These results are in accordance with the ones obtained by Takač et al (2015). Demir et al (2002) reported that the weight of 1000 seeds of eggplant ranged from 4 to 5 g and reached its maximum 70 days after fertilization.…”
Section: The Weight Of 1000 Seedssupporting
confidence: 92%
“…Therefore, germination of seed collected from reddish or dark-red fruits resulted in the best quality seeds. Several observations on different fruit maturation levels showed variations of effect on seed germination: the highest physiological quality of Jatropha curcas was attained when fruits became yellow (da Silva et al 2012), Solanum melongena seed's best quality occurred in mature fruit (Takač et al 2015), Gmelina arborea seeds from yellow brown fruits gave the best germinative performance (Adebisi et al 2012), I. wombolu seeds were best sown immediately after the fruits were harvested (Dolor 2011), sweet pepper (Capsicum annuum) seeds with high germination should be harvested when the outside of fruits are completely red (Vidigal et al 2011), Gmelina arborea seeds from yellow brown fruits gave the best germinative performance (Adebisi et al 2011), the physiological maturity of Cucurbita moschata seeds occurred on fruits maturity between 50 and 60 days after anthesis. The addition of soil to the rice husk could be a right step in the use of available RHC with agronomic benefits for vegetable production (Carter et al 2013).…”
Section: Seedling Growth In Different Growing Mediamentioning
confidence: 99%
“…Takač et al, 2015 utvrdili su uticaj faza sazrevanja ploda i dužine skladištenja plavog patlidžana na kvalitet semena. Seme plavog patlidžana posle prolaska faze dormantnosti, u skladišnim uslovima, dostiže uravnotežen nivo kvaliteta i životne sposobnosti (Demir et al 2002;2009,).…”
Section: Uvodunclassified